2007
DOI: 10.3163/1536-5050.95.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Realizing what's essential: a case study on integrating electronic journal management into a print-centric technicalservices department

Abstract: The serials staff now spends its time managing the materials most important to the library's clientele (e-journals and databases). The team's proactive approach to maintenance work and rapid response to reported problems should improve patrons' experiences using e-journals. The library is taking advantage of new technologies such as an electronic resource management system, and library workflows and procedures will continue to evolve as technology changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Early case studies of the shift to ER in academic library collections (Montgomery & Sparks, 2000;Duranceau, 1998;Gerhard, 1998) discuss, in varying degrees of detail, the development of new professional positions with a specialized focus on the tasks involved in the acquisition and management of these resources. Later studies appearing in the 2000s (Zhang & Haslam, 2005;Jasper & Sheble, 2005;Graves & Arthur, 2006;Dollar, Gallagher, Glover, Marone, & Crooker, 2007;Clendenning, Duggan, & Smith, 2010) described situations in which ERLs (or librarians in a related position) were already in place. The emphasis in these later discussions was generally on new workflows and adaptation of paraprofessional staff roles to new ways of managing technical services tasks and processes mainly related to electronic journals; they focused on the distribution of elements of the ERM workflow among retrained paraprofessional staff working under the guidance of the specialist librarian, with little attention to the specific workload on the librarians working in this area.…”
Section: Evolution Of Er Librarianshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Early case studies of the shift to ER in academic library collections (Montgomery & Sparks, 2000;Duranceau, 1998;Gerhard, 1998) discuss, in varying degrees of detail, the development of new professional positions with a specialized focus on the tasks involved in the acquisition and management of these resources. Later studies appearing in the 2000s (Zhang & Haslam, 2005;Jasper & Sheble, 2005;Graves & Arthur, 2006;Dollar, Gallagher, Glover, Marone, & Crooker, 2007;Clendenning, Duggan, & Smith, 2010) described situations in which ERLs (or librarians in a related position) were already in place. The emphasis in these later discussions was generally on new workflows and adaptation of paraprofessional staff roles to new ways of managing technical services tasks and processes mainly related to electronic journals; they focused on the distribution of elements of the ERM workflow among retrained paraprofessional staff working under the guidance of the specialist librarian, with little attention to the specific workload on the librarians working in this area.…”
Section: Evolution Of Er Librarianshipmentioning
confidence: 99%
“…The emphasis in these later discussions was generally on new workflows and adaptation of paraprofessional staff roles to new ways of managing technical services tasks and processes mainly related to electronic journals; they focused on the distribution of elements of the ERM workflow among retrained paraprofessional staff working under the guidance of the specialist librarian, with little attention to the specific workload on the librarians working in this area. Dollar, Gallagher, Glover, Marone, & Crooker (2007), and Clendenning, Duggan, & Smith (2010), however, did note that assigning various more routine ER acquisition-related responsibilities to paraprofessionals allowed librarians to focus on more complex tasks such as ERM system implementation, licensing, and e-journal package management.…”
Section: Evolution Of Er Librarianshipmentioning
confidence: 99%
“…His findings from a survey of mostly academic libraries found that there was "no clear pattern of an optimal organizational structure to enhance acquisitions and collection development activities" (409). Dollar, Gallagher, and Glover (2007) described the pressures on staff to deal with increasing electronic resources. The Technical Services Department changed names to become the Collection Development and Management Department, and the electronic resources librarian became associate director "to reflect its new emphasis on collections and managing electronic resources" (150).…”
Section: % and Climbingmentioning
confidence: 99%
“…1 In fact, a study of ARL research libraries reveals a decrease in print journal subscriptions from 64% in 2002 to 30% in 2006, an increase in both formats from 31% to 33%, and an increase in e-only formats from 5% to 37%. 2 While libraries in developed countries have achieved a greater level of success in the transition from print to electronic resources their experiences reveal that they encountered similar challenges that our libraries currently face.…”
Section: Literature Reviewmentioning
confidence: 99%